Specific combinations of ion channel inhibitors reduce excessive Ca2+ influx as a consequence of oxidative stress and increase neuronal and glial cell viability in vitro. (17th December 2016) - O'Hare Doig, Ryan L.; Bartlett, Carole A.; Smith, Nicole M.; Hodgetts, Stuart I.; Dunlop, Sarah A.; Hool, Livia; Fitzgerald, Melinda
Highlights: The effects of combinations of ion channel inhibitors on H2 O2 stressed cells were assessed in vitro . Most combinations of inhibitors with oxATP decreased Ca 2+ influx and increased cell viability. However, reductions in intracellular Ca 2+ concentration were not always linked to cell viability. Combinations of inhibitors preserved some cell subpopulations, particularly NG2+/olig2− glia. The data increase understanding of the efficacy of ion channel inhibitor combinations in vivo . Abstract: Combinations of Ca 2+ channel inhibitors have been proposed as an effective means to prevent excess Ca 2+ flux and death of neurons and glia following neurotrauma in vivo . However, it is not yet known if beneficial outcomes such as improved viability have been due to direct effects on intracellular Ca 2+ concentrations. Here, the effects of combinations of Lomerizine (Lom), 2, 3-dioxo-7-(1 H -imidazol-1-yl)6-nitro-1, 2, 3, 4-tetrahydro-1-quinoxalinyl]acetic acid monohydrate (YM872), 3, 5-dimethyl-1-adamantanamine (memantine (Mem)) and/or adenosine 5′-triphosphate periodate oxidized sodium salt (oxATP) to block voltage-gated Ca 2+ channels, Ca 2+ permeable α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptors, NMDA receptors and purinergic P2X7 receptors (P2X7 R) respectively, on Ca 2+ concentration and viability of rat primary mixed cortical (MC) cultures exposed to hydrogen peroxide (H2 O2 ) insult, were assessed. The contribution of ryanodine-sensitive intracellular stores to intracellular Ca 2+ concentration was also assessed. Live cell calcium imaging revealed that a 30 min H2 O2 insult induced a slow increase in intracellular Ca 2+, in part from intracellular sources, associated with loss of cell viability by 6 h. Most combinations of inhibitors that included oxATP significantly decreased Ca 2+ influx and increased cell viability when administered simultaneously with H2 O2 . However, reductions in intracellular Ca 2+ concentration were not always linked to improved cell viability. Examination of the density of specific cell subpopulations demonstrated that most combinations of inhibitors that included oxATP preserved NG2+ non-oligodendroglial cells, but preservation of astrocytes and neurons required additional inhibitors. Olig2 + oligodendroglia and ED-1 + activated microglia/macrophages were not preserved by any of the inhibitor combinations. These data indicate that following H2 O2 insult, limiting intracellular Ca 2+ entry via P2X7 R is generally associated with increased cell viability. Protection of NG2+ non-oligodendroglial cells by Ca 2+ channel inhibitor combinations may contribute to observed beneficial outcomes in vivo .